G(x) = 2x² - 5x + 2 = 2x² - 4x - x + 2 = 2x · x - 2x · 2 - 1 · x - 1 · (-2)
= 2x(x - 2) -1(x - 2) = (x - 2)(2x - 1)
g(x) = 0 ⇔ (x - 2)(2x - 1) = 0 ⇔ x - 2 = 0 or 2x - 1 = 0
x = 2 or x = 0.5
Answer:
48.75$
Step-by-step explanation:
the difference is about 16.25$
The answer is going to be 87.5%
Answer: m² + 3m - 10 = 0
Step-by-step explanation:
From the expression, considering
6x + 5 = m
The original expression
( 6x + 5 )² - 10 = -18 - 15
Factorize the right hand expression,
-18 - 15 = -3( 6x - 15 )
Since m = 6x + 5 , we now substitute for m in that expression
m² - 10 = -3m
Now re arrange the equation in the form,
ax² - bx + c = 0
Now back to the equation,
m² + 3m - 10 = 0,
So the equivalent equation will be
m² + 3m - 10 = 0
See attachment for the number line that compares the numbers 5.3, 5 1/5 and 5
<h3>How to plot the numbers on the number line?</h3>
The numbers are given as:
5.3, 5 1/5 and 5
We start by representing the numbers as decimals (i.e. real numbers).
So, we have:
5.3, 5.2 and 5
Reorder the numbers in ascending number (i.e. from least to greatest)
So, we have
5, 5.2 and 5.3
Next, we plot the numbers on a number line using a scale of 0.1
This can be visualized as
5 5.2 5.3
See attachment for the number line that compares the numbers 5.3, 5 1/5 and 5
Read more about number line at
brainly.com/question/24644930
#SPJ1